Adverse muscle composition is linked to poor functional performance and metabolic comorbidities in NAFLD - Jennifer Linge; Mattias Ekstedt; Olof Dahlqvist Leinhard (JHEP Reports, 2021)
Background & Aims: Sarcopenia and frailty are recognised as important factors in later stages of liver disease. However, their role in non-alcoholic fatty liver disease (NAFLD) is not yet fully understood. In this study we investigate the associations of MRI-measured adverse muscle composition (AMC: low muscle volume and high muscle fat) with poor function, sarcopenia, and metabolic comorbidity within NAFLD in the large UK Biobank imaging study. Methods: A total of 9,545 participants were included. Liver fat, fat-tissue free muscle volume, and muscle fat infiltration were quantified using a rapid MRI protocol and automated image analysis (AMRA® Researcher). For each participant, a personalised muscle volume z-score (sex- and body size-specific) was calculated and combined with muscle fat infiltration for AMC detection. The following outcomes were investigated: functional performance (hand grip strength, walking pace, stair climbing, falls) and metabolic comorbidities (coronary heart disease, type 2 diabetes). Sarcopenia was detected by combining MRI thresholds for low muscle quantity and low hand grip strength according to the European working group definition. Results: The prevalence of sarcopenia in NAFLD (1.6%) was significantly lower (p <0.05) compared with controls without fatty liver (3.4%), whereas the prevalence of poor function and metabolic comorbidity was similar or higher. Of the 1,204 participants with NAFLD, 169 (14%) had AMC and showed 1.7–2.4× higher prevalence of poor function (all p <0.05) as well as 2.1× and 3.3× higher prevalence of type 2 diabetes and coronary heart disease (p <0.001), respectively, compared with those without AMC. Conclusions: AMC is a prevalent and highly vulnerable NAFLD phenotype displaying poor function and high prevalence of metabolic comorbidity. Sarcopenia guidelines can be strengthened by including cut-offs for muscle fat, enabling AMC detection. Lay summary: Today, it is hard to predict whether a patient with fatty liver disease will progress to more severe liver disease. This study shows that measuring muscle health (the patient's muscle volume and how much fat they have in their muscles) could help identify the more vulnerable patients and enable early prevention of severe liver disease.